Estrous expression during a fixed-time artificial insemination protocol enhances development and interferon-tau messenger RNA expression in conceptuses from Bos indicus beef cows - Cooke, R. F.; Pohler, K. G.; Vasconcelos, J. L.M. [UNESP]; Cerri, R. L.A. (Elsevier, 2019)
Expression of estrus (EST) near the time of fixed-time artificial insemination (FTAI) increases pregnancy success in beef females. This outcome has been associated with improved pregnancy establishment and maintenance, although research is still warranted to validate this theory. Hence, this experiment compared ovarian, uterine and conceptus factors associated with pregnancy establishment in Bos indicus beef cows according to estrous expression during a FTAI protocol. One hundred lactating multiparous Nelore cows received a 2 mg injection of estradiol benzoate and an intravaginal progesterone (P4) releasing device on day '11, a 12.5 mg injection of prostaglandin F 2α on day '4, P4 device removal in addition to 0.6 mg injection of estradiol cypionate and 300 IU injection of equine chorionic gonadotropin on day '2, and FTAI on day 0. An estrous detection patch was attached to the tailhead of each cow on day '2, and estrous expression was defined as removal of >50% of the rub-off coating from the patch at FTAI. Overall, 39 cows expressed EST, 55 did not express EST (NOEST), and six cows lost their patch and were discarded from the experiment. Ovarian ultrasonography was performed at FTAI, and on days 7 and 15 of the experiment. Blood samples were also collected on days 7 and 15. Only cows without a corpus luteum (CL) on day 0, and with a CL on days 7 and 15 remained in the experiment (EST, n=36; NOEST, n=48). On day 15, cows were randomly selected within each group (EST, n=29; NOEST, n=30) for conceptus collection via transcervical flushing, followed by endometrial biopsy in the uterine horn ipsilateral to the CL. Within cows not assigned to conceptus collection, blood samples were collected for whole blood RNA extraction (day 20) and pregnancy status was verified by transrectal ultrasonography (day 30). Diameter of dominant follicle on day 0 and plasma P4 concentrations on day 7 were greater (P≤0.02) in EST v. NOEST cows. Conceptus length and messenger RNA (mRNA) expression of prostaglandin E synthase and interferon-tau were greater (P≤0.04) in EST v. NOEST cows. Moreover, EST cows diagnosed as pregnant on day 30 had greater (P<0.01) blood mRNA expression of myxovirus resistance 2 on day 20 compared with NOEST. In summary, estrous expression near the time of FTAI enhanced pregnancy establishment factors in B. indicus cows, including conceptus development and mRNA expression of interferon-tau.
Keywords: beef cattle; insemination; physiology; pregnancy; reproduction